Effects of Qing Qiao Capsule in the treatment of chronic secretory otitis media and the levels of serum inflammatory factors - Zhong, Lunkun; Tan, Minhua; Hu, Wenjian; Lv, Caifeng; Zhu, Jiali; Liu, Jing; Zhou, Xingwei (Cellular and Molecular Biology, 2020)
To explore the effects of Qing Qiao Capsule in the treatment of chronic secretory otitis media and the levels of serum inflammatory factors, a total of 50 chronic secretory otitis media patients in the control group were subjected to caefaclor capsule, while the total of 50 cases in the observation group were treated with Qing Qiao Capsule. The traditional Chinese medicine (TCM) syndrome scores, therapeutic effects, and the levels of inflammatory factors were evaluated. After treatment, the scores of deafness, hearing loss, dizziness, soreness and weakness of the waist and knees, and fever is hens in palms and soles were significantly decreased in both groups (all P value <0.05). However, each score in the observation group was markedly less than that of the control group (all P value <0.05). Moreover, the C-reactive protein (CRP), procalcitonin (PCT) and tumor necrosis factor-Î± (TNF-Î±) levels measured after treatment were significantly lowered than those before treatment (all P value <0.05). Also, the levels of CRP, PCT and TNF-Î± in the observation group were obviously less than that of the control group (all P value <0.05). And the total therapeutic efficacy of the observation group was significantly higher than that of the control group (P<0.05). But no significant difference was observed in the rates of adverse reactions between both groups (P>0.05). Application of Qing Qiao Capsule in the treatment of chronic secretory otitis media yields better results, lowers TCM syndrome scores, and alleviates the body’s inflammatory response, which is a safe drug in clinical use.